Optimization of System Authentication Services using Blockchain Technology - Imam Riadi; Herman Herman; Aulyah Zakilah Ifani (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2021)
With the development of the era, one thing that must be considered for security is the Login System. In most cases, user login information is stored on the server. This gives access to sensitive informatio, many hackers easily break into data from users. Based on these problems, this research focuses on data security authentication in the form of usernames and passwords in the login system. Authentication using blockchain is used to reduce malicious access and increase security for the authentication process. One of the innovative technologies that can solve these problems is Blockchain Technology. Using blockchain technology, hackers will find it difficult to change and modify the same data on all computers at the same time because it takes a very long time to crack the encryption code on each block of data in the entire computer network. Data storage or transactions in the blockchain are stored in the form of hashes. This makes it difficult for hackers to break into it. Tests in this study using Wireshark tools and network miner. Based on the research conducted, the test was conducted as many as 5 times with two scenarios, namely authentication of the login system before using the blockchain and after using the blockchain. The results obtained. The, system built using blockchain can secure data. The test results obtained that data in the form of usernames and passwords were converted into hashes and with the immutable nature of the blockchain, data from users could not be changed or replaced by anyone.